Effects on growth, membrane integrity, and phytoremediation potential of Arachis pintoi in soil with excess boron - de Souza, Roberta Possas [UNESP]; Sakurai, Tiely [UNESP]; de Camargos, Liliane Santos [UNESP] (Springer Nature, 2025)
Boron (B) is a micronutrient that plays a structural role in the cell wall and the correct functioning of the plasma membrane; however, excess B in soil is an emerging environmental problem that can hinder plant development. In this context, phytoremediation, which uses plants to contain, destroy, or extract pollutants from the environment, presents a sustainable solution. Therefore, this study aimed to evaluate the growth, membrane integrity, and phytoremediation potential of forage peanuts (Arachis pintoi Krapov. & W. C. Greg.) grown in soil with high concentrations of B. The experiment was carried out in a greenhouse, under a completely randomized design, using 6 concentrations of B (0.5, 30, 60, 90, 120, and 150 mg B dm−3 soil) in the form of boric acid and 6 replicates for each treatment. After 60 days of cultivation, increasing B doses resulted in a decline in the number of leaves, root dry mass, fresh mass, and number of nodules. Arachis pintoi was tolerant to up to 60 mg B dm−3 of soil and a high rate of B translocation was observed, so that B accumulation was predominant in the shoots. Furthermore, damage to cell membranes intensifies from 90 mg B dm−3 soil. In conclusion, A. pintoi is tolerant to excess B up to a 60 mg B dm−3 soil dose and can be classified as a phytoextractor when accumulating B in the shoots. However, boron toxicity causes oxidative damage and impairs growth, limiting its establishment in more severely contaminated environments.